Acute subdural hematoma and diffuse axonal injury in fatal road traffic accident victims: a clinico-pathological study of 15 patients Hematoma subdural agudo e lesão axonal difusa em vítimas fatais de acidente de trânsito: estudo clínico-patológico de 15 pacientes - Sebastião Nataniel Silva Gusmão; José Eymard Homem Pittella (Arquivos de Neuro-Psiquiatria)
OBJECTIVE: Although acute subdural hematoma (ASDH) and diffuse axonal injury (DAI) are commonly associated in victims of head injury due to road traffic accidents, there are only two clinico-pathological studies of this association. We report a clinical and pathological study of 15 patients with ASDH associated with DAI. METHOD: The patients were victims of road traffic accidents and were randomly chosen. The state of consciousness on hospital admission was evaluated by the Glasgow coma scale. For the identification of axons the histological sections of the brain were stained with anti-neurofilament proteins. RESULTS: Twelve of the 15 patients were admitted to hospital in a state of coma; in three patients, the level of consciousness was not evaluated, as they died before hospital admission. CONCLUSION: The poorer prognosis in patients with ASDH who lapse into coma immediately after sustaining a head injury, as described by several authors, can be explained by the almost constant association between ASDH and DAI in victims of fatal road traffic accidents. OBJETIVO: Embora o hematoma subdural agudo (HSDA) e a lesão axonal difusa (LAD) estejam frequentemente associados em vítimas de trauma crânio-encefálico causado por acidentes de trânsito, há somente dois estudos clínico-patológicos sobre esta associação. Relatamos o estudo clínico-patológico de 15 pacientes com HSDA associado com LAD. MÉTODO: Os pacientes, vítimas de acidentes de trânsito, foram selecionados aleatoriamente. O estado de consciência à admissão hospitalar foi avaliado pela escala de coma de Glasgow. Para a identificação dos axônios, os cortes histológicos do cérebro foram corados com antisoro anti-proteínas do neurofilamento. RESULTADOS: Doze dos 15 pacientes foram admitidos no hospital em estado de coma; em três pacientes, o nível de consciência não foi avaliado, pois eles faleceram antes da admissão hospitalar. CONCLUSÃO: O pior prognóstico em pacientes com HSDA que apresentam coma imediatamente após serem admitidos por trauma crânio-encefálico, como descrito por vários autores, pode ser explicado pela quase que constante associação entre HSDA e LAD em vítimas fatais de acidentes de trânsito.